The Effect of REKIS Innovation in Increasing The Resilience of Mothers Who Have Stunted Children - Grhasta Dian Perestroika; Niken Bayu Argaheni; Rizka Ayu Setyani; Mustikaningtyas; Titi Ngudiati; Fika Lilik Indrawati (Universitas Nahdlatul Ulama Surabaya, 2023)
The community still perceives stunting as a negative stigma. It potentially risks the mental health of both the child and the mother. Mother resilience is crucial to deal with biopsychosocial stressors because of stunting. This research analyzes the effects of the REKIS (Resiliensi Komunitas Ibu Dengan Anak Stunting) innovation on knowledge, attitudes, behavior, and resilience regarding stunting in mothers with stunted children. This research was a quantitative study with a quasi-experimental design. The population was mothers with children diagnosed with stunting in the Gilingan Surakarta Health Center. There were 60 respondents with the total sampling technique, 30 in the control and 30 in the intervention groups. Pre-test and post-test data were collected using knowledge, attitude, behavior, and maternal resilience questionnaires. Data analysis used the Wilcoxon Rank Sum Test to test the difference in mean scores between the control and intervention groups. In addition, the Wilcoxon Signed Rank Test analyzes the difference in mean scores between the pre-and post-test. The results showed that all respondents had similar demographic characteristics (age, occupation, and education). Both groups had significant differences in pre and post-test mean scores on maternal knowledge, attitudes, behavior, and resilience (p<0.05). Significant differences were in the overall pre- and post-test mean scores on maternal knowledge, attitudes, and resilience (p<0.05). However, there was no significant difference in the pre-and post-test on maternal behavior. In conclusion, The REKIS innovation can increase the resilience of mothers with stunted children. It improves maternal knowledge and attitudes regarding stunting.